Impact of COVID‐19 pandemic on acute heart failure admissions and mortality: a multicentre study (COV‐HF‐SIRIO 6 study). (16th November 2021) - Kubica, Jacek; Ostrowska, Małgorzata; Stolarek, Wioleta; Kasprzak, Michał; Grzelakowska, Klaudyna; Kryś, Jacek; Kubica, Aldona; Adamski, Piotr; Podhajski, Przemysław; Navarese, Eliano Pio; Anielska‐Michalak, Edyta; Brycht, Oliwia; et al.
Abstract: Aims: The coronavirus disease‐2019 (COVID‐19) pandemic has changed the landscape of medical care delivery worldwide. We aimed to assess the influence of COVID‐19 pandemic on hospital admissions and in‐hospital mortality rate in patients with acute heart failure (AHF) in a retrospective, multicentre study. Methods and results: From 1 January 2019 to 31 December 2020, a total of 101 433 patients were hospitalized in 24 Cardiology Departments in Poland. The number of patients admitted due to AHF decreased by 23.4% from 9853 in 2019 to 7546 in 2020 ( P  < 0.001). We noted a significant reduction of self‐referrals in the times of COVID‐19 pandemic accounting 27.8% ( P  < 0.001), with increased number of AHF patients brought by an ambulance by 15.9% ( P  < 0.001). The length of hospital stay was overall similar (7.7 ± 2.8 vs. 8.2 ± 3.7 days; P  = not significant). The in‐hospital all‐cause mortality in AHF patients was 444 (5.2%) in 2019 vs. 406 (6.5%) in 2020 ( P  < 0.001). A total number of AHF patients with concomitant COVID‐19 was 239 (3.2% of AHF patients hospitalized in 2020). The rate of in‐hospital deaths in AHF patients with COVID‐19 was extremely high accounting 31.4%, reaching up to 44.1% in the peak of the pandemic in November 2020. Conclusions: Our study indicates that the COVID‐19 pandemic led to (i) reduced hospital admissions for AHF; (ii) decreased number of self‐referred AHF patients and increased number of AHF patients brought by an ambulance; and (iii) increased in‐hospital mortality for AHF with very high mortality rate for concomitant AHF and COVID‐19.